How valuable is physical examination of the cardiovascular system?. (27th July 2016) - Elder, Andrew; Japp, Alan; Verghese, Abraham
Abstract : Physical examination of the cardiovascular system is central to contemporary teaching and practice in clinical medicine. Evidence about its value focuses on its diagnostic accuracy and varies widely in methodological quality and statistical power. This makes collation, analysis, and understanding of results difficult and limits their application to daily clinical practice. Specific factors affecting interpretation and clinical application include poor standardisation of observers' technique and training, the study of single signs rather than multiple signs or signs in combination with symptoms, and the tendency to compare physical examination directly with technological aids to diagnosis rather than explore diagnostic strategies that combine both. Other potential aspects of the value of physical examination, such as cost effectiveness or patients' perceptions, are poorly studied. This review summarises the evidence for the clinical value of physical examination of the cardiovascular system. The best was judged to relate to the detection and evaluation of valvular heart disease, the diagnosis and treatment of heart failure, the jugular venous pulse in the assessment of central venous pressure, and the detection of atrial fibrillation, peripheral arterial disease, impaired perfusion, and aortic and carotid disease. Although technological aids to diagnosis are likely to become even more widely available at the point of care, the evidence suggests that further research into the value of physical examination of the cardiovascular system is needed, particularly in low resource settings and as a potential means of limiting inappropriate overuse of technological aids to diagnosis.